(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the introduction of innovative approaches to the teaching of natural (Science) sciences in general education schools and the importance of innovative technologies in ensuring the effectiveness of education is highlighted. Also, the history of innovations, definitions of pedagogic scientists who conducted scientific research on innovative technologies, opinions on important aspects of using innovative technologies in teaching natural sciences are presented.